Principal's Strategy in Managing Tahfiz Learning - Azmil, Isna Amalia; Kaltsum, Honest Ummi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to explain the principal's strategy in developing Tahfiz Qur'an learning at MI Miftahul Ulum Ringinlarik. Data sources were obtained from teachers, students, and vice curriculum at MI Miftahul Ulum Ringinlarik. Observation, interviews, and documentation carry out data collection techniques. The MI Miftahul Ulum Ringinlarik observation stage was carried out in January 2023 and finished in February 2023. During the interview, principals, managers, teachers, and students were respondents at MI Miftahul Ulum Ringinlarik. At the Documentation stage, activities, lesson plans, and syllabi have been collected to become data on the strategy of managing the Tahfiz program as a flagship program at MI Miftahul Ulum Ringinlarik. Data analysis was carried out with the stages of data reduction, data presentation, conclusion, and verification. The study results show that the school principal's role in managing the Tahfiz program at MI Miftahul Ulum Ringinlarik is carried out by implementing a cluster system known as the madrasa system, which is carried out intensively. The principal's strategy in managing the Tahfiz program at MI Miftahul Ulum Ringinlarik is carried out by setting significant goals and analyzing the current conditions and situation at the planning stage. To support the implementation of the Tahfiz program, school principals make improvements to teaching staff, school facilities, and infrastructure and monitor program implementation. Evaluation of program stages at the end of the school year with establishing standards and methods for measuring teacher performance, comparing results with established standards/targets, and taking corrective action by identifying supporting and inhibiting factors.